DEVELOPMENT AND APPLICATIONS OF MICRO-AND NANOROBOTICS IN DRUG DELIVERY - DHYANI, ARCHANA; BHATT, JYOTSNA; SINGH, NARDEV; DHYANI, ASHISH (International Journal of Applied Pharmaceutics, 2023)
Micro-and nanorobotics is a new field of research that emerged from the fusion of micro/nanotechnology and robotics and has since acquired enormous importance. The advantages of micro-and nanorobots include their small dimension, lightweight, high flexibility, and high sensitivity. Micro-and nanorobots have sparked the scientific community's interest in research and opened up a broad variety of application areas, including medication delivery and disease diagnostics, due to their differences from macroscopic robots. Over the past 30 y, research on micro-and nanorobots has made major strides. This manuscript provides a detailed explanation of the development of these robots. Then, each of the primary robot components including their actuation, design, production, and control is discussed separately. Additionally, potential challenges in developing such robots are explored from the perspectives of intelligence and sensing, therapeutic applications, materials, and performance.